Sequence of a Complete Chicken BG Haplotype Shows Dynamic Expansion and Contraction of Two Gene Lineages with Particular Expression Patterns - Salomonsen, Jan (Public Library of Science, 2014)
Many genes important in immunity are found as multigene families. The butyrophilin genes are members of the B7 family, playing diverse roles in co-regulation and perhaps in antigen presentation. In humans, a fixed number of butyrophilin genes are found in and around the major histocompatibility complex (MHC), and show striking association with particular autoimmune diseases. In chickens, BG genes encode homologues with somewhat different domain organisation. Only a few BG genes have been characterised, one involved in actin-myosin interaction in the intestinal brush border, and another implicated in resistance to viral diseases. We characterise all BG genes in B12 chickens, finding a multigene family organised as tandem repeats in the BG region outside the MHC, a single gene in the MHC (the BF-BL region), and another single gene on a different chromosome. There is a precise cell and tissue expression for each gene, but overall there are two kinds, those expressed by haemopoietic cells and those expressed in tissues (presumably non-haemopoietic cells), correlating with two different kinds of promoters and 5′ untranslated regions (5′UTR). However, the multigene family in the BG region contains many hybrid genes, suggesting recombination and/or deletion as major evolutionary forces. We identify BG genes in the chicken whole genome shotgun sequence, as well as by comparison to other haplotypes by fibre fluorescence in situ hybridisation, confirming dynamic expansion and contraction within the BG region. Thus, the BG genes in chickens are undergoing much more rapid evolution compared to their homologues in mammals, for reasons yet to be understood.